Competing on Platforms - Cutolo, Donato; Hargadon, Andrew; Kenney, Martin (MIT Sloan Management Review, 2021)
Doing business on the dominant digital platforms makes it difficult for companies to differentiate their products and services and pursue competitive strategy. Platform-dependent businesses must understand the risks and how to navigate them.